Apakah Transfer Pricing Mempengaruhi Pajak? : Tinjauan Sistematis - Sulthan Yusuf Abdullah; Memen Kustiawan; Ida Farida Adi Prawira (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Transfer Pricing become a problem in its application to some countries because it affects state revenue. Some companies apply Transfer pricing to avoid paying taxes. The purpose of this study is to aims does transfer pricing has an effect on the taxes paid by the company with the focus of the research answering the question "Does the application of transfer pricing have an impact on tax payments". This question will be answered in this article, using the Systematic Literature Review research method by reviewing several international and national standard journals that have been published under 5 years, starting from 2016 to 2021. This study finds that the application of transfer pricing in various companies both within both domestically and abroad are used as a tool for tax evasion, but companies in developed countries focus on tax compliance. The limitations of the research include the time required to review more articles is very limited, the number of reference articles used as sources is not much. However, this research is expected to expand information and knowledge about Transfer Pricing and can be used as a reference for further research.